Tinjauan Efektifitas Perhitungan Zakat Mall Dalam Sistem Informasi Masjid - Puji Subekti, Puji Subekti; Andini, Titania Dwi; Islamiyah, Mufidatul (Sekolah Tinggi Ilmu Komputer PGRI Banyuwangi, 2024)
Zakat is an obligation that must be fulfilled by Muslims when their wealth reaches the nisab and haul thresholds. There are several types of zakat, namely zakat mall and zakat fitrah. These zakat funds can be distributed to the needy by zakat distribution institutions. In reality, the zakat distribution mechanism is still carried out manually in some institutions, especially mosques. Mosques should ideally have information systems that can provide information about activities and services, including zakat distribution services. Therefore, a web-based mosque activity information system was developed, equipped with zakat mall calculation and distribution. The system was developed using Hypertext Preprocessor (PHP), Laravel framework, and MySQL database, aiming to facilitate zakat distribution institutions in providing information without manual intervention. The information system was tested using data collection techniques involving questionnaires and observations. The research stages include needs analysis, system design, implementation, and testing. The questionnaire testing results, conducted with a total of 30 respondents through a presentation followed by questionnaire filling via Google Form, showed that 90% of the system could meet user needs